Generative AI in Software Development Education: Insights from a Degree Apprenticeship Programme - Olga Petrovska (UKICER '23: Proceedings of the 2023 Conference on United Kingdom & Ireland Computing Education, 2023)
We describe insights gained from incorporating ChatGPT into assignments for our Software Engineering Degree Apprenticeship programme, including attitudes expressed by the learners and their employers regarding our approach.